The Characterization and Therapeutic Targeting of CD133 in Human Glioblastoma - Salim, Sabra (My University, 2021)
CD133, a pentaspan glycoprotein, has long been known to represent aggressive, stem-like populations across various human malignancies. While its expression correlates with numerous clinical outcomes including disease progression, metastasis, recurrence, and poor overall survival in numerous cancers, little is currently known about its function. In the brain cancer glioblastoma (GBM), CD133-expressing cells have previously been shown to initiate tumours, evade therapy and interestingly, self-renew, a key property of cancer stem cells. With an implied signalling role in driving self-renewal, we aim to elucidate the role of CD133 in glioblastoma. To understand the role of CD133, we aim to study its protein-protein interactions using the proximity-dependent labelling technique known as miniTurboID. By tagging proteins of interest with a promiscuous biotin ligase at both protein termini, potential interactors can be biotinylated and identified by subsequent mass spectrometry. While miniTurboID has traditionally been performed by synthetic transgenes expressing the tagged proteins of interest in commercial cell lines, overexpression may not recapitulate its native function. Thus, using CRISPR technology, we aim to insert the miniTurboID ligase at both the N- and C-terminus of CD133 in patient-derived human GBM lines. Although little is currently known about CD133 function, development of targeted therapies has presented a promising strategy in pre-clinical studies. In the Singh Lab, we previously developed a chimeric antigen receptor T-cell, or CAR-T, comprised of a T-cell expressing a synthetic receptor capable of recognizing a tumor-associated antigen and activating cytolytic-killing directed towards the target cell. Currently, CAR-T therapies are autologous, or patient-derived, in nature which may host a myriad of concerns including patient-specific qualitative and quantitative T-cell dysfunction, inconsistent generation of CAR products, and availability to rapidly progressing patients. To circumvent this concern, “off-the-shelf”, donor-derived or allogeneic CAR-T products may be generated for use in GBM patients. However, in addition to CAR integration, allogeneic products must be additionally modified to eradicate expression of the endogenous TCR, as this would induce a phenomenon known as graft versus host disease, in which healthy tissues are targeted. Thus, in this thesis, we show gene editing potential in human GBMs to perform an endogenous genomic knock-in of miniTurboID. With the identification of interacting proteins, defining the subsequent functionality of CD133 may elucidate oncogenic cellular programs, and highlight common nodes of interaction within divergent cell signaling pathways. To develop an allogeneic CAR-T product, we designed a two-step approach in which the CAR sequence was integrated into the TCR gene for simultaneous knock-out. We later show early pre-clinical efficacy in comparison to traditional autologous CAR-T in our patient-derived models of human GBM. Thus, by using CD133 as a centralizing concept in this thesis, we ultimately hope to develop our biological understanding of CD133, while testing the therapeutic development of a donor-derived CAR-T therapy.
Keywords: Cancer; Glioblastoma; BioID; Proteins; CAR-T; Immunotherapy; Allogeneic; T-cell; CD133; Brain tumor initiating cells; Cancer stem cells